Valorization in recycling actions: an experience with women in a mini-market - França, Luana Pereira de; Lopes, Liliane Duran; Brandalise, Loreni Teresinha; Bertolini, Geysler Rogis Flor (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
This study seeks to assess whether women, customers of a mini-market in São José das Palmeiras/PR, value sustainability actions related to recycling and separation of solid waste. To this end, a quasi-experimental research was conducted, whose purpose was to monitor the change in perception of the target audience of the research before and after the intervention. The quasi-experiment was developed in three moments. It was observed that most women consumers do not value sustainability actions, but after the intervention, there was an increase of women who started to separate the waste in their homes.